STEM Learning with a Simple Hydraulic Pump Project to Improve Student Communication and Collaboration Skills - Amri, Muhammad Fahriza; Prima, Eka Cahya; Winarno, Nanang; Mohamad, Maslawati (Universitas Negeri Semarang, 2024)
To succeed in today's era, a person must possess 21st-century skills, which include communication and collaboration. With a Simple Hydraulic Pump project, this study aims to enhance students' communication and collaboration skills through STEM learning at the junior high school level. This quantitative study applied a quasi-experimental approach with a pretest-posttest control group research design. The participants are 38 out of 228 8th-grade students in two junior high schools in Bandung, Indonesia. Statistical analyses using the Wilcoxon Signed Rank tests were done on the data obtained through pretests and posttests. The results indicate a non-significant gain in communication skills of students in the experimental group compared to the control group, with a significance value of 0.67 (sig. >0.05), meaning that there is a non-significant difference between pretest and posttest results. Meanwhile, the collaboration skills of students in the experimental group increased significantly compared to the control group, with a significance value of 0.03 (sig. <0.05), indicating a significant difference between the pretest and posttest results. Using Cohen’s d, it is evident that students’ collaboration skills experience a medium increase (r=0.22). Furthermore, students’ communication and collaboration skills were measured using the Performance Assessment Rubric. The results demonstrate that STEM learning using a simple hydraulic pump project can enhance students’ collaboration skills but not their communication skills. This implies that while STEM learning helps students improve their collaboration skills, other methods are needed to assist them in developing their communication skills.